2016
DOI: 10.1039/c6gc00977h
|View full text |Cite
|
Sign up to set email alerts
|

A study of poplar organosolv lignin after melt rheology treatment as carbon fiber precursors

Abstract: Lignins from various poplar genotypes were isolated by using organosolv fractionation and subjected to rheological treatment at various temperatures. Physicochemical characterization of the lignin variants shows a broad distribution of glass transition temperatures, melt viscosity, and pyrolysis char residues.Rheological treatment at 170°C induces lignin repolymerization accompanied with an increase in condensed linkages, molecular weights, and viscosities. In contrast, rheology testing at 190°C results in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 41 publications
3
88
3
1
Order By: Relevance
“…Previously, Sun et al 48 investigated rheology of softwood lignin at different melting temperatures and indicated that repolymerization is the main reaction at temperatures below 190 8C, and thermal decomposition becomes dominant at higher temperatures. Since meltspinning of lignin is usually conducted at a temperature range below 200 8C (because aryl ether linkages in lignin cleave at temperatures above 200 8C), the mass loss of the precursors at this temperature range could be indicative of undesired bubbling and volatile release during the melt-spinning process.…”
Section: Glass Transition Temperaturementioning
confidence: 99%
“…Previously, Sun et al 48 investigated rheology of softwood lignin at different melting temperatures and indicated that repolymerization is the main reaction at temperatures below 190 8C, and thermal decomposition becomes dominant at higher temperatures. Since meltspinning of lignin is usually conducted at a temperature range below 200 8C (because aryl ether linkages in lignin cleave at temperatures above 200 8C), the mass loss of the precursors at this temperature range could be indicative of undesired bubbling and volatile release during the melt-spinning process.…”
Section: Glass Transition Temperaturementioning
confidence: 99%
“…[2a] Our group learned previously that thermals tabilization in air can crosslink lignin with itself or with acrylonitrile-butadiene rubber( NBR),g iving different thermomechanical properties of the lignin-NBRadducts, hinting to apathway for bettercontrol of morphology. [10] Concurrently,l ignin radicals can also attack the unsaturated C=Co nN BR, in turn, crosslinking with NBR. As ag ood radicals cavenger, [9] any free radicals generatedf rom the thermally sensitive linkages during stabilization can then crosslink with reactive sites on other lignin molecules, resulting in am olecular weight change.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal viscosity measured at 200 °C is also shown in the figure. Isothermal viscosity can reflect the processability of the precursor fibers during melt‐spinning process . As shown in Figure (d), the viscosity is initially within 10–50 Pa·s for all three polymers.…”
Section: Resultsmentioning
confidence: 99%